DETERMINAN LOYALITAS NASABAH KPR PT.BANK MANDIRI, TBK CABANG SURABAYA - Wilma Cordelia Izaak (Jurnal MEBIS (Manajemen dan Bisnis), 2018)
The purpose of this study was to determine the influence of perceived quality as well as perceived value of consumers, or in this case the consumers of house mortgages over their satisfaction and loyalty. The respondents being analyzed are the consumers of house mortgages in one government bank located in Surabaya. The tool used for analyzing is the Partial Least Square model obtained through the software SmartPLS version 2.0.M3. To sum up, the result of the hypothetical analyzes shows that both perceived quality and perceived value have no indirect influence over loyalty through satisfaction. The lack of influence that perceived value as well as perceived quality indirectly and directly over loyalty can be explained as a growing phenomenon. This phenomenon sees the tendency for consumers of mortgage to choose bank with the best environment’s house as their place of living (and not as an investment), and also the availability of guarantee for their mortagages in long terms.